Heavy Metals Biosorption by Powdered Rhizopus Oligosporus Biomass - Ling, Tau Chuan (1997)
The biosorption of several metals by powdered biomass of Rhizopus oligosporus was investigated. Cells of Rhizopus olzgosporus were cultured, harvested, washed, oven dried and mixed in solutions containing lead, copper, cadmium and aluminium ions. After an equilibration period, the biomass was separated from the metal bearing solution and the content of heavy metals were determined by an Atomic Adsorption Spectrophotometer. The biosorption of metal ions was increased with increasing initial concentration of heavy metal. The heavy metal uptake capacity increased in the order: copper (73.50 mg/g) > lead (60.90 mg/g) > cadmium (30.15 mg/g) > aluminium (26.60 mg/g). Langmuir Adsorption Model was suitable for describing the biosorption of lead, cadmium, aluminium and copper. Reciprocal Langmuir Transformation and Scatchard analysis revealed that different types of binding sites are involved in the biosorption process. pH regulation of the process can enhance the biosorption capacity for all metals tested The optimum pH for lead, cadmium, aluminum and copper are 5, 4, 4 and 6 respectively The possibility for desorption the metals from loaded biomass usmg HCI and NaOH were tested The desorption efficiency for HCl and NaOH increased with Increasing concentration of HCl and NaOH HCl was more efficient than NaOH The possibility of removing heavy metal from industrial wastes was also investigated For electroplating wastes, the heavy metals uptake capacities Increased m the order lead (0.44 mg/g) > cadmium (0.11 mg/g) > copper (0.09 mg/g) For aluminum wastes, the heavy metals uptake capacities increased In the order cadmium (0.12 mg/g) > copper (0.10 mg/g).